Method for preparing high-frequency low-loss MnZn power ferrite material by introducing lanthanide ions at low cost
By introducing lanthanide ions and low-cost rare earth oxides, combined with the use of auxiliary components, the problems of high loss of MnZn ferrite materials under high frequency conditions and difficult production cost control are solved, and high-frequency, low-loss and low-cost MnZn power ferrite materials are achieved.
Patent Information
- Application Number
- CN202510091591.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
AI Technical Summary
The existing MnZn ferrite materials have high loss characteristics under high frequency conditions, which affects the efficiency and service life of electronic components. At the same time, production cost control is difficult, especially in the selection of dopants.
By introducing lanthanide ions, low-cost rare earth oxides are used to replace high-cost rare earth oxides, combined with Ta2O5, CaO, Dy2O3, and Ce2O3 as auxiliary components, ball milling, prefiring, granulation and sintering are carried out to prepare high-frequency and low-loss MnZn power ferrite materials.
The low loss performance of MnZn ferrite material at 1MHz frequency is achieved, which reduces eddy current loss, improves the resistivity of grain boundaries and grains, extends the service life of the material, and reduces production costs.
Smart Images

Figure CN119822805A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a high-frequency and low-loss MnZn power ferrite material by introducing lanthanide ions at low cost, belonging to the technical field of ferrite material preparation. Background Art
[0002] The vigorous development of new technologies such as new energy vehicles, 5G communications, and big data has promoted the development of the electronics industry and put forward higher requirements for electronic components. As one of the most important components of electronic components, the performance of MnZn power ferrite directly affects the working state of electronic components. In order to realize the high-frequency and miniaturized application of electronic components, the performance of MnZn ferrite materials under high-frequency conditions must be improved. Among them, the high-frequency loss characteristics are directly related to the efficiency and service life of electronic components. Therefore, the development of a low-loss MnZn power ferrite at MHz frequency is of great significance to the upgrading and development of materials and the electronics industry.
[0003] In the increasingly competitive magnetic material market, for MnZn ferrite manufacturers, in addition to pursuing more excellent performance to meet the ever-changing market demand and the stringent requirements of high-end applications, the control of production costs is also a key issue for MnZn ferrite manufacturers. The cost control of MnZn ferrite involves many aspects, but it mainly focuses on the selection of dopants. Different dopants have different effects on improving the performance of MnZn ferrite, and their prices also vary greatly. Therefore, for manufacturers, among the many dopants, selecting dopants that can significantly improve product performance and have the advantage of low cost can reduce production costs while ensuring product quality, thereby achieving better production benefits and occupying a more advantageous position in market competition.
[0004] Therefore, the present invention provides a low-cost, high-performance, widely used MnZn power ferrite material and its preparation process. By introducing rare earth oxides, low-cost rare earth oxides are used to replace high-cost rare earth oxides, the production cost is reduced, and the advantages of composite rare earth doping are brought into play. The prepared MnZn ferrite shows good performance at a frequency of 1MHz, which is of great significance for industrial production. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing a high-frequency and low-loss MnZn power ferrite material by introducing lanthanide ions at a low cost.
[0006] The technical solution of the present invention is as follows:
[0007] A high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions, comprising a main component and an auxiliary component;
[0008] The main components, in terms of mass percentage, include: Fe2O3 68.0-69.4wt%, Mn3O4 22.8-23.8wt%, ZnO 7.6-8.0wt%, with a total amount of 100wt%;
[0009] The mass content of the auxiliary components in the main component is: Ta2O5 1400-1800ppm, CaO 200-600ppm, Dy2O30-500ppm, Ce2O3 150-500ppm.
[0010] Preferably, according to the present invention, the main components, in terms of molar percentage, include: Fe2O3 69wt%, Mn3O4 23wt%, ZnO 8wt%, with a total amount of 100wt%;
[0011] The mass contents of the auxiliary components in the main components are: Ta2O5 1600ppm, CaO 400ppm, Dy2O3 250ppm, Ce2O3 250ppm.
[0012] The method for preparing the high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions comprises the following steps:
[0013] (1) weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, performing a ball milling treatment, and then drying the ball milled slurry to obtain the main component powder;
[0014] (2) pre-calcining the main component powder obtained in step (1), and cooling it to obtain a main component pre-calcined material;
[0015] (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, CaO, Dy2O3, and Ce2O3 according to the proportion, performing a secondary ball milling treatment, and then drying the ball milled slurry to obtain a mixed powder;
[0016] (4) adding a polyvinyl alcohol aqueous solution to the mixed powder obtained in step (3), uniformly granulating the mixed powder in a mechanical granulator, and sieving the mixed powder to obtain a granular material;
[0017] (5) The granular material obtained in step (4) is pressed and sintered in sequence to obtain a high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions.
[0018] Preferably, in step (1), the primary ball milling is carried out in a ball mill, the ball milling time is 60 to 70 min, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 3:1:1, and the ball mill speed is 280 to 320 rpm.
[0019] Preferably according to the present invention, in step (1), the average particle size of the main component powder is ≤1.1 μm.
[0020] Preferably according to the present invention, in step (2), the pre-firing temperature is 900-1000° C. and the time is 1.5-2.5 hours.
[0021] Preferably, according to the present invention, in step (3), the secondary ball milling is carried out in a ball mill, the ball milling time is 300-400 min, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 5:1:1, and the ball mill speed is 330-370 rpm.
[0022] Preferably according to the present invention, in step (3), the average particle size of the mixed powder is 1 to 1.2 μm.
[0023] Preferably, according to the present invention, in step (4), the mass concentration of the polyvinyl alcohol aqueous solution is 3-5%, and the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is (5-10):100.
[0024] Preferably according to the present invention, in step (4), the granulation time is 100 to 200 seconds, and the granulation rotation speed is 5000 to 6000 r.
[0025] Preferably according to the present invention, in step (5), the pressing is performed at 400 MPa to form a magnetic ring.
[0026] Preferably, according to the present invention, in step (5), the sintering is to place the magnetic ring in a sintering device, sinter at 1160-1200°C in a mixed gas of 3.5% O2+96.5% N2 for 25-35 minutes, and then cool to below 300°C.
[0027] Further preferably, the sintering is to sinter the magnetic ring at 1180° C. for 30 minutes.
[0028] The above-mentioned high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions is used in the fields of aerospace or automotive electronics.
[0029] Anything not described in detail in the present invention can be carried out according to the prior art.
[0030] Technical features and beneficial effects of the present invention:
[0031] 1. The present invention provides a high-frequency, low-loss MnZn power ferrite material, wherein the auxiliary components Ta2O5, CaO, Dy2O3, and Ce2O3 enter the MnZn ferrite lattice, modify the MnZn ferrite, affect the ion distribution in the lattice, and increase the intracrystalline resistance. At the same time, after entering the lattice, the lanthanide rare earth ions will be segregated at the grain boundary, which will increase the grain boundary resistivity and limit the growth of grains, and will also weaken the electronic transition conduction mechanism, increase the grain resistance, and thus reduce the eddy current loss. Since the eddy current loss is dominant in the medium and high frequency loss, the reduction of the eddy current loss reduces the total loss.
[0032] 2. The present invention reduces the amount of high-cost Dy2O3 by increasing the amount of low-cost Ce2O3. The loss of the prepared MnZn power ferrite is 179kW·m under the test conditions of 1MHz, 30mT and 25℃. -3 , is a potential material that can be used in the MHz-level high-frequency field, which helps to solve the problems of high loss, high heat generation, low efficiency and short material life at high frequencies. And due to the addition of Ta2O5, CaO, Dy2O3 and Ce2O3, the grain size is reduced, which helps to reduce the total loss. The addition of multiple ions changes the microscopic composition of ferrite materials and changes the electromagnetic properties of materials, which is conducive to reducing losses. At the same time, considering the cost of additives in large-scale production, the use of lower-cost Ce2O3 can ensure performance while reducing production costs, providing a new idea and new method for the research and development of magnetic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The XRD diagrams of the MnZn power ferrites prepared in Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention are shown.
[0034] Figure 2 This is a cross-sectional morphology of the MnZn ferrite material prepared in Example 1.
[0035] Figure 3 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 1.
[0036] Figure 4 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0037] The present invention is further described below by specific examples and drawings, but the scope of the present invention is not limited. The raw materials used in the examples are all conventional raw materials, and the equipment used is all conventional equipment, which can be purchased from the market.
[0038] Example 1
[0039] A high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions, comprising a main component and an auxiliary component;
[0040] The main components, in terms of molar percentage, include: Fe2O3 69wt%, Mn3O4 23wt%, ZnO 8wt%;
[0041] The mass contents of the auxiliary components in the main components are: Ta2O5 1600ppm, CaO 400ppm, Dy2O3 250ppm, Ce2O3 250ppm.
[0042] The method for preparing the high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions comprises the following steps:
[0043] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they are ball-milled in a ball mill for 65 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water is 3:1:1, and the speed of the ball mill is 300 rpm; then the ball-milled slurry is dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;
[0044] (2) pre-calcining the main component powder obtained in step (1) at 950° C. for 2 hours, and naturally cooling to room temperature to obtain a main component pre-calcined material;
[0045] (3) According to the proportion, the main component pre-sintered material obtained in step (2) is mixed with the auxiliary component raw materials Ta2O5, CaO, Dy2O3, and Ce2O3, and a secondary ball milling treatment is performed in a ball mill. The ball milling time is 350 minutes. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1, and the ball mill speed is 350 rpm; then the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm;
[0046] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500 r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;
[0047] (5) The granular material obtained in step (4) is pressed into a 26*16*5mm magnetic ring green body at 400MPa, and then the magnetic ring green body is placed in a sintering device, sintered at 1180°C in a nitrogen and oxygen mixed gas of 3.5% O2+96.5% N2, and cooled to below 300°C in nitrogen and the magnetic ring is taken out to obtain a high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions.
[0048] Example 2
[0049] A high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions, comprising a main component and an auxiliary component;
[0050] The main components, in terms of molar percentage, include: Fe2O3 69wt%, Mn3O4 23wt%, ZnO 8wt%;
[0051] The mass contents of the auxiliary components in the main components are: Ta2O5 1600ppm, CaO 400ppm, Ce2O3 150ppm, and Dy2O3 350ppm.
[0052] The method for preparing the high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions comprises the following steps:
[0053] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they are ball-milled in a ball mill for 60 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water is 3:1:1, and the speed of the ball mill is 320 rpm; then the ball-milled slurry is dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;
[0054] (2) pre-calcining the main component powder obtained in step (1) at 1000° C. for 1.5 hours, and naturally cooling to room temperature to obtain a main component pre-calcined material;
[0055] (3) According to the proportion, the main component pre-sintered material obtained in step (2) is mixed with the auxiliary component raw materials Ta2O5, CaO, Dy2O3, and Ce2O3, and a secondary ball milling treatment is performed in a ball mill. The ball milling time is 300 min. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1, and the ball mill speed is 370 rpm; then the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm;
[0056] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500 r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;
[0057] (5) The granular material obtained in step (4) is pressed into a 26*16*5mm magnetic ring green body at 400MPa, and then the magnetic ring green body is placed in a sintering device, sintered at 1180°C in a nitrogen and oxygen mixed gas of 3.5% O2+96.5% N2, and cooled to below 300°C in nitrogen and the magnetic ring is taken out to obtain a high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions.
[0058] Example 3
[0059] A high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions, comprising a main component and an auxiliary component;
[0060] The main components, in terms of molar percentage, include: Fe2O3 69wt%, Mn3O4 23wt%, ZnO 8wt%;
[0061] The mass contents of the auxiliary components in the main components are: Ta2O5 1600ppm, CaO 400ppm, Ce2O3 350ppm, and Dy2O3 150ppm.
[0062] The method for preparing the high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions comprises the following steps:
[0063] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they are ball-milled in a ball mill for 70 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water is 3:1:1, and the speed of the ball mill is 280 rpm; then the ball-milled slurry is dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;
[0064] (2) pre-calcining the main component powder obtained in step (1) at 900° C. for 2.5 hours and naturally cooling to room temperature to obtain a main component pre-calcined material;
[0065] (3) According to the proportion, the main component pre-sintered material obtained in step (2) is mixed with the auxiliary component raw materials Ta2O5, CaO, Dy2O3, and Ce2O3, and a secondary ball milling treatment is performed in a ball mill. The ball milling time is 400 min. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1, and the ball mill speed is 330 rpm; then the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm;
[0066] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500 r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;
[0067] (5) The granular material obtained in step (4) is pressed into a 26*16*5mm magnetic ring green body at 400MPa, and then the magnetic ring green body is placed in a sintering device, sintered at 1180°C in a nitrogen and oxygen mixed gas of 3.5% O2+96.5% N2, and cooled to below 300°C in nitrogen and the magnetic ring is taken out to obtain a high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions.
[0068] Example 4
[0069] A high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions, comprising a main component and an auxiliary component;
[0070] The main components, in terms of molar percentage, include: Fe2O3 69wt%, Mn3O4 23wt%, ZnO 8wt%;
[0071] The mass content of the auxiliary components in the main component is: Ta2O5 1600ppm, CaO 400ppm, Ce2O3500ppm.
[0072] The specific preparation method is the same as that in Example 1.
[0073] Comparative Example 1
[0074] A MnZn power ferrite material, comprising a main component and an auxiliary component;
[0075] The main components, in terms of molar percentage, include: Fe2O3 69wt%, Mn3O4 23wt%, ZnO 8wt%;
[0076] The mass content of the auxiliary components in the main component is: Ta2O5 1600ppm, CaO 400ppm, Dy2O3500ppm.
[0077] The specific preparation method is the same as that in Example 1.
[0078] Comparative Example 2
[0079] A MnZn ferrite material, whose specific composition and preparation method are as described in Example 1, except that it does not contain auxiliary components.
[0080] Test example
[0081] 1. XRD characterization and loss (P cv ) test, and the results are shown in Table 1.
[0082] 2. The specific test method is: using LCR-8210 digital bridge at 1V voltage and 1MHz to measure the initial magnetic permeability (μ i The loss P of the products prepared in Examples 1 to 4 and Comparative Examples 1 to 2 at 1 MHz, 30 mT, and 25°C was tested using a soft magnetic AC measuring instrument (MAST-3000SA). cv .
[0083] Table 1. Product performance of Examples 1 to 4 and Comparative Examples 1 to 2
[0084] sample <![CDATA[Initial permeability (μ i )]]> <![CDATA[P cv (1MHz,30mT,25℃)]]> Example 1 952 179 Example 2 867 198 Example 3 878 199 Example 4 835 214 Comparative Example 1 821 196 Comparative Example 2 613 1485
[0085] Depend on Figure 1 It can be seen that the samples prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 have only one phase of MnZn ferrite after XRD detection, indicating that the preparation method provided by the present invention can successfully prepare MnZn ferrite material. And the addition of dopants will not change the phase composition of MnZn ferrite.
[0086] It can be seen from Table 1 that, compared with Comparative Example 2, the high-frequency, low-loss MnZn power ferrite materials introduced with lanthanide ions in Examples 1 to 4 of the present invention have significantly reduced losses at 1MHz, 30mT, and 25°C, and significantly increased initial magnetic permeability. This shows that the preparation method provided by the present invention effectively improves the performance of the MnZn ferrite material by controlling the introduction of lanthanide ions through doping, so that the MnZn ferrite material prepared by the present invention has both high-frequency, low-loss and high magnetic permeability characteristics. By comparing Examples 1 to 4 with Comparative Example 1, it can be seen that by replacing the high-cost Dy2O3 with the low-cost Ce2O3, not only the preparation cost can be reduced, but also the magnetic permeability of the material can be significantly improved, the loss can be reduced, and the performance can be improved, so that the application frequency band of MnZn ferrite can be expanded to the MHz level, and the added value of the product can be increased at a lower cost. Among them, Example 1 is the formula with the best comprehensive performance in the experiment, and it can be applied to large-scale production.
[0087] That is, the high-frequency, low-loss MnZn power ferrite material prepared in Example 1 is modified by adding Ta2O5, CaO, Ce2O3, and Dy2O3 as auxiliary components to modify MnZn ferrite, and multiple ions form a high-resistance layer at the grain boundary, which increases the grain boundary resistivity, inhibits grain growth, and reduces eddy current loss. At the same time, after the lanthanide rare earth ions enter the lattice, they will weaken the electronic transition conduction mechanism and increase the grain resistance, which will also reduce the eddy current loss.
[0088] 2. The morphology of the products prepared in Example 1, Comparative Example 1 and Comparative Example 2 was observed using a scanning electron microscope (SEM). The results are as follows: Figures 2 to 4 shown.
[0089] Depend on Figures 2 to 4 It can be seen that the grain size of the MnZn ferrite material prepared in Example 1 is smaller than that in Comparative Example 1, and is significantly smaller than that in Comparative Example 2. Due to the addition of Ta2O5, CaO, Dy2O3, and Ce2O3, the grain size is significantly smaller than that in Comparative Example 2, and the eddy current radius is reduced, which is helpful to reduce the total loss. In addition, the addition of multiple ions changes the microscopic composition of the ferrite material, changes the electromagnetic properties of the material, and is conducive to reducing the loss.
[0090] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify or replace the technical solution of the present invention with equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high-frequency, low-loss MnZn power ferrite material into which lanthanide ions are introduced, characterized in that: Includes main components and auxiliary components; The main components, in terms of mass percentage, include: Fe2O3 68.0-69.4wt%, Mn3O4 22.8-23.8wt%, ZnO 7.6-8.0wt%, with a total amount of 100wt%; The mass content of the auxiliary components in the main component is: Ta2O5 1400-1800ppm, CaO 200-600ppm, Dy2O30-500ppm, Ce2O3 150-500ppm.
2. The high-frequency, low-loss MnZn power ferrite material with lanthanide ions introduced as claimed in claim 1, characterized in that: The main components, in terms of molar percentage, include: Fe2O3 69wt%, Mn3O4 23wt%, ZnO 8wt%, with a total amount of 100wt%; The mass contents of the auxiliary components in the main components are: Ta2O5 1600ppm, CaO 400ppm, Dy2O3 250ppm, Ce2O3 250ppm.
3. The method for preparing the high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions as claimed in claim 1 comprises the following steps: (1) weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the ratio, performing a ball milling treatment, and then drying the ball milled slurry to obtain the main component powder; (2) pre-calcining the main component powder obtained in step (1), and cooling it to obtain a main component pre-calcined material; (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, CaO, Dy2O3, and Ce2O3 according to the proportion, performing a secondary ball milling treatment, and then drying the ball milled slurry to obtain a mixed powder; (4) adding a polyvinyl alcohol aqueous solution to the mixed powder obtained in step (3), uniformly granulating the mixed powder in a mechanical granulator, and sieving the mixed powder to obtain a granular material; (5) The granular material obtained in step (4) is pressed and sintered in sequence to obtain a high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions.
4. The preparation method according to claim 3, characterized in that: In step (1), the primary ball milling is carried out in a ball mill, the ball milling time is 60 to 70 minutes, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 3:1:1, and the ball mill speed is 280 to 320 rpm; the average particle size of the main component powder is ≤1.1 μm.
5. The preparation method according to claim 3, characterized in that: In step (2), the pre-firing temperature is 900-1000° C. and the pre-firing time is 1.5-2.5 hours.
6. The preparation method according to claim 3, characterized in that: In step (3), the secondary ball milling is carried out in a ball mill, the ball milling time is 300 to 400 minutes, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 5:1:1, and the ball mill speed is 330 to 370 rpm; the average particle size of the mixed powder is 1 to 1.2 μm.
7. The preparation method according to claim 3, characterized in that: In step (4), the mass concentration of the polyvinyl alcohol aqueous solution is 3-4%, and the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is (5-10):
100.
8. The preparation method according to claim 3, characterized in that: In step (4), the granulation time is 100 to 200 seconds, and the granulation rotation speed is 5000 to 6000 r.
9. The preparation method according to claim 3, characterized in that: In step (5), the pressing is performed at 400 MPa to form a magnetic ring; the sintering is performed by placing the magnetic ring in a sintering device, sintering it at 1160-1200° C. in a mixed gas of 3.5% O2+96.5% N2 for 25-35 minutes, and then cooling it to below 300° C.; Further preferably, the sintering is to sinter the magnetic ring at 1180° C. for 30 minutes.
10. Application of the high-frequency, low-loss MnZn power ferrite material introduced with lanthanide ions as claimed in claim 1 in the fields of aerospace or automotive electronics.